Surgicoanatomical aspect in vascular variations of the V3 segment of vertebral artery as a risk factor for C1 instrumentation. (October 2019) - Arslan, Dilek; Ozer, Mehmet Asim; Govsa, Figen; Kitis, Omer
Highlights: Anomalies in VA is crucial to avoid injuries during surgical procedure. During C2 transpedicular screwing of VA with vascular abnormality simply high risk of VA injury. The preoperative 3D-CTA evaluation is mandatory to reach safety corridor for VA. The right side should be preferred first with the screw insertion to the more solid C2 bony elements. Abstract: Object: Awareness of vascular anomalies in V3 segment of vertebral artery (VA) is crucial to avoid iatrogenic injuries during surgical procedure. This study aimed to analyze the incidence of V3 segment vascular variations and demonstrate the importance of deciding the surgical strategy for C1 screw placement. Methods: Prevalence of vascular variations and morphometric measurements of the VA in the region of the craniocervical junction in 200 cases based on three-dimensional computed tomographic angiography (3D-CTA) scans were studied. Results: The VA has a variable course through C2 before it passes above its groove on the posterior arch of C1. Following the vascular variations of V3 segments of VA were persistent including first intersegmental artery (FIA), fenestration (FEN) of the VA, high-riding (HRVA and the posterior inferior cerebellar artery (PICA) branch originating from the C1/2 part of VA. HRVA was observed in 10.1% of patients, FIA in 1.8%, FEN in 1.3%, and PICA in 1.3%. One hundred and twenty-three (24.1%) patients were identified to have HRVA, 6% present on both sides. Conclusion: The VA with FIA and FEN were rare in this study as many as a 10% the VA present over the starting point for C1 lateral screw. With respect to the vascular anatomy of V3 and more frequent left-sided VA dominancy, standard screw insertion should be started from the right side. Routine preoperative 3D-CTA evaluation is mandatory to prevent the VA injury when C1-C2 instrumentation is planned.